Membangun Karakter Disiplin pada Anak melalui Pendidikan Keluarga - Faddia Risalah Achmad; Restina Oktavia; Rina Anggraeni; Siti Zahra; Uswatun Hasanah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
Family education is the main education for children because the family has an important role in forming a child's disciplined character. The approach used is not always in the form of punishment, but in other ways, for example by modeling good behavior, inviting children to make agreements and carry them out, etc., implementing clear and consistent house rules, etc. Parents themselves play an important role in shaping children's disciplined character as educators, role models, motivators and supervisors. The agreement made is: Parental parenting styles also have an influence on the development of children's discipline. The method used in this research is using a library research approach (Library Research) with qualitative methods. Thus, family education is a determining factor in the formation of a child's disciplined character.